2017
DOI: 10.2147/opth.s129830
|View full text |Cite
|
Sign up to set email alerts
|

Corneal flap thickness with the Moria M2 single-use head 90 microkeratome in 72 consecutive LASIK procedures

Abstract: PurposeThis study aimed to evaluate the accuracy and consistency of corneal flap thickness in laser-assisted in situ keratomileusis (LASIK) with the Moria M2 single-use head 90 microkeratome.MethodsThe central corneal thickness of 72 (37 right, 35 left) eyes of 37 patients was measured by ultrasonic pachymetry preoperatively and intraoperatively after flap cut. The Moria M2 single-use head 90 microkeratome was used to create a superior hinged flap in all eyes. The right eyes were always operated on before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Currently, LASIK is the most popular surgery to treat refractive error. [ 1 2 3 4 ] It is safe and effective to use LASIK to treat refractive amblyopia. [ 5 6 7 8 9 ] However, the perioperative suction can cause elevation of the IOP to a level greater than 65 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, LASIK is the most popular surgery to treat refractive error. [ 1 2 3 4 ] It is safe and effective to use LASIK to treat refractive amblyopia. [ 5 6 7 8 9 ] However, the perioperative suction can cause elevation of the IOP to a level greater than 65 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Laser in situ keratomileusis (LASIK) has been widely used to treat refractive error in adults since 1990. [ 1 2 3 4 ] It is safe and effective for the treatment of amblyopia because of severe anisometropia in children. [ 5 6 7 8 9 ] Previous studies have shown mild, reversible, and localized macular edema and thinning of the retinal nerve fiber layer (RNFL) soon after LASIK in adults.…”
Section: Introductionmentioning
confidence: 99%
“…The Moria-Plus SBK microkeratome forms a corneal flap with a nasal hinge of 8.5-9.0 mm in diameter. This device is utilized to test a central flap thickness of 110 m with a head accuracy of 90 m [5].…”
Section: Introductionmentioning
confidence: 99%
“…First critical step during LASIK surgery is creation of successful flap of adequate thickness. 5 Excellent LASIK outcomes require safe, predictable, and reproducible flap parameters. 6,7 Great attention must be given to improve the predictability and to minimize the degree of variation in corneal flap thickness, which is directly related to LASIK predictability and safety.…”
Section: Introductionmentioning
confidence: 99%